Selves Engraved on Stone: Seals and Identity in the Ancient Near East, ca. 1415-1050 BCE - Yalcin, Serdar (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
Typically carved in stone, the cylinder seal is perhaps the most distinctive art form to emerge in ancient Mesopotamia. It spread across the Near East from ca. 3300 BCE onwards, and remained in use for millennia. What was the role of this intricate object in the making of a person's social identity? As the first comprehensive study dedicated to this question, Selves Engraved on Stone explores the ways in which different but often intersecting aspects of identity, such as religion, gender, community and profession, were constructed through the material, visual, and textual characteristics of seals from Mesopotamia and Syria.